ANALYSIS OF THE POWER OF LAW ORAL AGREEMENT ON LAND SALE (STUDY OF DECISION NUMBER 51/Pdt.G/2011/PN.PRA) - Arum Puspita Rois, Diandra Kis; Sutrisno (Universitas Islam Balitar, 2024)
The power of law is proof that an agreement has been created and the value of this engagement in front of the law, the power of law becomes uncertain if an agreement made verbally and contains a offense. In this analysis, we will focus on verbal agreements on buying and selling land by reviewing the Case Study of Decision Number: 51/Pdt.G/2011/PN.PRA. The research was carried out using a normative method, namely legal research by reviewing literature based on books, laws and decisions of the District Court. Based on the principles that form the principle of the creation of agreements along with the meaning in Article 1320 of the Civil Code where an agreement is considered valid if it fulfills 4 conditions in the article, then Article 1338 paragraph (1) explains that an agreement that has been legally created must apply as a law for the creators of the agreement, and can declare one of the member to have committed an unlawful act if the evidence and witnesses provided can convince the consideration of the Panel of Judges. Keywords: Legal Strength, Spoken Agreement, Sale And Purchase Of Land.